English Lecturers’ Perception of Learning Model In Merdeka Belajar Kampus Merdeka (MBKM) Curriculum Implementation - Farouk Imam Arrasyid (International Journal of Education and Humanities, 2023)
The learning model in the MBKM curriculum includes its own provisions that enable the MBKM curriculum's aims such as student-centered learning and fostering 21st century skills. The goal of this study is to see if the provisions of the government's suggested learning model are consistent with its use in classroom English instruction. as well as English lecturers' perceptions of the learning model's application in the MBKM curriculum. This is a qualitative research method. Observation and interviews are two methods for gathering data. The instruments to be utilized include observation checklists and semi-structured interviews. The researcher discovered that the government's suggested learning model is consistent with its implementation in the classroom, allowing lecturers to be more effective in their teaching and adapt to the needs of their pupils. Furthermore, English lecturers from both Tadris Bahawa Inggris (TBI) and Pusat Pengembangan Bahasa (PPB) applauded the incorporation of the MBKM curriculum into the learning paradigm